Inhibition of Knee Osteoarthritis Progression in Mice by Administering SRT2014, an Activator of Silent Information Regulator 2 Ortholog 1. (December 2021) - Miyaji, Nobuaki; Nishida, Kyohei; Tanaka, Toshikazu; Araki, Daisuke; Kanzaki, Noriyuki; Hoshino, Yuichi; Kuroda, Ryosuke; Matsushita, Takehiko
Objective: Previous findings suggest that silent information regulator 2 ortholog 1 (SIRT1) plays essential roles in chondrocytes and prevents osteoarthritis (OA) development. The purpose of this study was to investigate the effects of intraperitoneal (i.p.) and intra-articular (i.a.) administration of the SIRT1 activator SRT2104, which has been approved for use in humans. Design: OA was induced by destabilizing the medial meniscus in the knee joint of 12-week-old CL57BL/6J mice. The mice were divided into 3 groups, that is, the control group, SRT2104 i.p.-injection group, and SRT2104 i.a.-injection group. Tissues were harvested at 4, 8, 12, and 16 weeks postsurgery. OA progression was evaluated using the Osteoarthritis Research Society International (OARSI) score. The production of OA-related proteins in cartilage and synovium was examined by immunohistochemistry. Results: OARSI scores in the control group were significantly higher at 8 and 12 weeks compared with other 2 groups. Immunohistochemical analysis showed that Sirt1 and type-2 collagen significantly increased, whereas MMP-13, ADAMTS-5, IL-1β, IL-6, cleaved caspase 3, PARP p85, acetylated NF-κB p65, and iNOS decreased significantly in cartilage tissues from the i.p. and i.a, SRT2104 groups. In the synovium, more iNOS-positive M1-like macrophages were observed in the control group than in the i.p. and i.a, SRT2104 groups, whereas more CD206-positive M2-like macrophages were detected in the i.p. and i.a. SRT2104 groups. Conclusions: Both i.p. and i.a. SRT2104 injection reduced OA progression in the mouse OA model, suggesting that SRT2104 can serve as a new treatment for OA.